(Invited) Si Photonics and Recent Challenges for on-Chip WDM. (14th September 2015) - Wada, Kazumi; Zhang, Z.; Yako, M.; Ju, K.; Kawai, N.J.
Abstract : The present paper proposes a new platform of Si photonics for on-chip dense wavelength division multiplexing (DWDM). The proposed SiNx platform deposited by physical vapor deposition (PVD-SiNx ) is robust against thermal fluctuation on a Si chip because of its small thermo-optics coefficient of SiNx . The presented platform can be fabricated in the CMOS back-end-of-line and only needs bulk Si wafers.